Regional Issue Identification and Assessment Program (RIIA). Socioeconomic impacts of proposed power plants in the northeast: issue paper 1 - W., Metz. (Brookhaven National Laboratory, 1979)
Each new major electric generating facility during its construction and operation periods presents a variety of social and economic consequences to the local, state, and regional areas. The potential for delay due to socioeconomic factors and the economic costs and benefits associated with proposed power plants are described with regard to two energy development scenarios: (1) Department of Energy National Energy Plan I and (2) a utility plan composite. Only proposed power plants with capacities over 400 MW and slated for completion by 1990 located in the three eastern federal regions (1, 2, and 3) are included.